2018
DOI: 10.3168/jds.2017-14010
|View full text |Cite
|
Sign up to set email alerts
|

Preweaned heifer management on US dairy operations: Part I. Descriptive characteristics of preweaned heifer raising practices

Abstract: The objective of this study was to describe preweaned dairy heifer calf management practices on dairy operations across the United States that were used to analyze factors associated with colostrum quality and passive transfer, Cryptosporidium and Giardia, morbidity and mortality, and average daily gain. This study included 104 dairy operations in 13 states that participated in the National Animal Health Monitoring System's Dairy 2014 calf component study. This 18-mo longitudinal study focused on dairy heifer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 34 publications
2
85
4
1
Order By: Relevance
“…The number of diarrheal days was significantly correlated with the intensity of the Cryptosporidium infection indicating that the parasite was responsible for diarrhea in the present study. In contrast, a considerably higher ADG (700 g) at an average weaning age of 66 days was reported for dairy calves in a large-scale US study; however, here clinical signs had been seen in only 38% of the animals, including 21% with digestive signs (Urie et al, 2018b). Although the HALO treatment showed a partial anticryptosporidial activity, it had no clinical effect in the present study: it did not significantly affect the onset, nor the frequency, duration and intensity of diarrhea, the main clinical symptom of cryptosporidiosis.…”
Section: Bodyweight Gain and Diarrheacontrasting
confidence: 62%
“…The number of diarrheal days was significantly correlated with the intensity of the Cryptosporidium infection indicating that the parasite was responsible for diarrhea in the present study. In contrast, a considerably higher ADG (700 g) at an average weaning age of 66 days was reported for dairy calves in a large-scale US study; however, here clinical signs had been seen in only 38% of the animals, including 21% with digestive signs (Urie et al, 2018b). Although the HALO treatment showed a partial anticryptosporidial activity, it had no clinical effect in the present study: it did not significantly affect the onset, nor the frequency, duration and intensity of diarrhea, the main clinical symptom of cryptosporidiosis.…”
Section: Bodyweight Gain and Diarrheacontrasting
confidence: 62%
“…Dairy operations were categorized based on the number of mature cows, as small (30 to 99 cows), medium-sized (100 to 499 cows), and large (500 or more cows). Figures describing the study sample and operations can be found in Urie et al (2018a).…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal diarrhea is a major source of economic loss in the dairy industry and the leading cause of preweaning calf mortality in most countries (Reiten et al, 2018;Urie et al, 2018). Treatment primarily focuses on correcting dehydration, increasing blood pH to correct the acidemia, restoring electrolyte concentrations and providing nutritional support (Smith and Berchtold, 2014).…”
Section: Introductionmentioning
confidence: 99%